Evolutionary and humanistic response to the challenges of modernity - Vodopianov, Pavel A. (Journal of the Belarusian State University. Sociology, 2025)
The main directions of activities to achieve a secure future on the way to overcome global threats of modernity are outlined. It is indicated that the formation of moral and ideological orientations on the basis of global evolutionism is important. The necessity of establishing a new type of morality, understood as responsibility for the preservation of life, is substantiated. Measures to optimise the population, overcome social inequality, prevent environmental pollution, as well as to preserve living space, natural resources and biological diversity are presented.